The use of some mixtures of medicinal plant ethanol extracts as an antifungal in the control of peanut stem rot diseases - Herwita Idris; Anthoni Agustien; Mansyurdin (Results in Engineering)
This study aims to determine the effectiveness of antifungal formulations and concentrations made from several ethanol extracts of medicinal plants that are appropriate against Athelia rolfsii which causes peanut stem rot disease, in August-December 2023 in the Parasitology Laboratory of the Laing Solok Experimental Garden. The research was arranged in a completely randomised design in factorial, using 2 methods, namely: (1) suppression of colony diameter using Patato Dextrose Agar media (2) suppression of colony biomass using Potato Dextrose Broth media. The treatments tested were ethanol extracts of medicinal plants Andrographis paniculata, Piper aduncum, Uncaria gambir, a mixture of A. paniculata extract + P. aduncum extract; A. paniculata extract + P. aduncum extract + U. gambir extract; P. aduncum extract + U. gambir extract; A. paniculata extract + U. gambir extract; synthetic fungicides and no treatment as a comparison. The concentration levels tested were 2 %, 3 % and 4 %. The results of the study showed that the species that causes peanut stem rot disease is Athelia rolfsii. From the results of GC–MS analysis, the dominant compounds of ethanol extract of A. paniculata (9-Octadecen-1-ol, (Z); Hexadecanoic acid; Octadecanoic acid), extract of P. aduncum was (1,3 Benzodioxole,4,5 dimethoxi; 1,1,4,4-tetramethyl-2‑hydroxy-7-e, while the dominant U. gambir extract was (9-Hexadecenoic acid Hexadecanoic acid; 2,5-Octadecadrynoic acid-methylc). The ethanol extract of A. paniculata single formulation as well as the mixed extract at 4 % concentration were more fungicidal than P. aduncum and U. gambir single formulations except the mixed formulation of A. paniculata extract + U. gambir extract which was worse than synthetic fungicides in suppressing the growth of diameter and biomass of A. rolfsii colonies. The mixed formulation of A. paniculata extract + P. aduncum extract + U. gambir extract showed the highest effectiveness of all formulations tested at each concentration, providing inhibition of colony diameter and biomass growth (91.07 % and 100.00 %). So that the ethanol extracts of the tested medicinal plants have the potential to be a promising anti-fungal alternative to replace chemical fungicides that are very dangerous.